Study On Commercial Offer And Services Offered By Non-Eu Citizens - Gómez Adillón M. Jesús; Cabasés Piqué M. Angels; Ortiz Pastor Maria (European Regional Science Association (ERSA), 2013)
In the last few years, one of the effects of the immigration phenomenon occurred in Spanish cities has been the growing of commercial offer and services with establishments whose owners are non-EU citizens. In this view, and focused on the city of Lleida, this article aims to analyse the socioeconomic profile of the owners of the abovementioned activities, as well as, the characteristics of their customers, and the channels of distribution, location and specialization of their establishments so as to propose ways to improve local commercial fabric. The methodology of this paper is based on statistical methods. It collects interviews and meetings with experts. It also includes surveys to do an empirical study from a sample of establishments. First, it carries out a descriptive analysis of variables grouped together under six main blocks: (a) general data on the establishments (b) specific data (c) technical data (d) owner?s personal data (e) facility data and (f) other statistically qualitative variables. Further, there is an in-depth study in the knowledge of differences statistically relevant, such as those observed in the surface area of those establishments according to owner?s nationality. This is accomplished by a segmentation analysis, which sets apart two types of activities: trading and services. Finally, this study puts into practice a multiple correspondence analysis will allow to evaluate establishments with two dimensions. One will reveal patterns of establishments run by African people, located near the historic centre, and close to each other. The other will show business of the services sector, with a typology of native customers and high geographic dispersion by districts. At the same time, the cartographic analysis shows the location for the commercial offer and services provided, pointing out areas of the municipality where the clustering of a particular typology of establishments is noticed. The research shows, on one side, that remarkable differences are found depending on the nationality of the entrepreneur and the type of customers. On the other side, it reveals differences in the location of the establishments, most of them in the historic city centre. However, it is worth stressing that the integration of economic activities performed by foreigners is viewed as positive. In this sense, there are measures to promote economic activities regardless the nationality of the entrepreneur. Also, initiatives are launched to bolster commercial association, and to facilitate the relationship of this typology of establishments with their geographical environment.
Keywords: 330; commercial offer; services offer; immigration; urban planning